Globalisation and jurisdiction (Kluwer Law International, 2004)
In this book, the legal developments in some selected sectors which display particularly interesting features, such as international securities and banking and the internet are addressed. For every sector the question can be asked: what are the challenges posed by globalisation and how has the law been reacting to them? An overview of these developments provides valuable input for the second purpose of this book, the academic debate on jurisdiction and globalisation. Which problems are encountered? To what extent have traditional concepts of jurisdiction accommodated the requirements of a global economy? To what extent have these traditional concepts been adapted and new ones developed to solve these problems?